Ảnh hưởng của phương pháp tổng hợp đến tính chất cấu trúc của nhôm oxit. Tiềm năng ứng dụng làm chất mang của nhôm oxit mao quản trung bình có trật tự - Thu Hà, Vũ Thị; Hải, Đỗ Thanh; Ngọ, Đinh Thị (Vietnam Journal of Chemistry, 2014)
In the present work, the synthesis methods of alumina as a support for catalytic applications have been carried out by us. We show that the synthetic way to alumina is the starting point that determines the micro- and macrostructure of the oxide and, consequently, allows control of the support characteristics. Usually, conventional aluminas with surface areas of 50 - 300 m2/g are manufactured by precipitation method. Transition aluminas (α, γ, δ, η, θ) that were prepared by heat treatment of different aluminium oxide-hydroxide precursors (e.g. boehmite, pseudoboehmite, bayerite, nordstrandite) usually exhibit surface areas lower than 350 - 400 m2/g and their main disadvantage is in their broad pore size distribution. Recently, well-ordered mesoporous aluminas with surface areas exceeding 350 m2/g and having narrow pore size distribution were synthesized in our laboratory. This support exhibited significantly higher capacity for dispersion of active species than the conventional alumina and they have a certain potential in catalytic applications